Burkitt Lymphoma/Leukemia Presented on 68Ga-Pentixafor and 18F-FDG PET/CT. (January 2022) - Chen, Zhenying; Xue, Qianqian; Huang, Chao; Yao, Shaobo; Miao, Weibing
Abstract : Abstract: An 18-year-old man with newly diagnosed Burkitt lymphoma/leukemia was referred for 18 F-FDG and 68 Ga-Pentixafor PET/CT. 68 Ga-Pentixafor PET/CT revealed similar radioactivity uptake pattern to the 18 F-FDG PET/CT in superior phrenic lymph node, ascending colon, ileocecum, peritoneal, marrow, and spleen. This case highlighted that it might be interesting to further investigate the role of 68 Ga-Pentixafor PET/CT imaging in staging, treatment evaluation, and especially the feasibility of CXCR4-directed radioligand therapy in Burkitt lymphoma with positive expression of CXCR4.